THE INFLUENCE OF HUMAN CAPITAL RECRUITMENT STRATEGIES ON THE COMPETITIVENESS OF SMALL AND MEDIUM-SIZED PRACTICES (SMPs) IN UGANDA - Otete, Albert Richards (International Journal of Entrepreneurship and Project Management, 2018)
Purpose: Small and Medium-sized Practice (SMPs) firms are growing exponentially in Uganda. SMPs are all the professional accounting firms, excluding the Big-4 (Deloitte, EY, KPMG and PwC). The objective of the study was to determine the influence of human capital recruitment strategies on the competitiveness of SMPs in Uganda. Methods: A random sample of 140 SMPs in Uganda was selected. In each firm, a partner who is well versed with the business responded to the questionnaire. The research design was cross-sectional using a quantitative approach. A total of 112 complete case questionnaires were used in the data analysis; an effective response rate of 80%. The null hypothesis was that human capital recruitment strategies do not have a significant influence on the competitiveness of SMPs in Uganda. Results: 65% of the SMPs were less than 8 years old implying they have more than doubled since the year 2010. The sample was adequate for factor analysis with a Kaiser-Meyer-Olkin (KMO) statistic of 0.70 and the structured questionnaire was deemed reliable using Cronbach Î± of at least 0.76 for each of two scales. Bartlett test of sphericity was used to confirm that the variables were not intercorrelated while the Variance inflation factors <5.0 indicated no problems with multicollinearity of the independent variables. The average full-time complement of partners/staff was 14 per firm. 75% of the SMPs had less than that number. Professional experience of partners/staff was rated as the most critical measure of competitiveness of an SMP. Unique contribution to theory, practice and policy: SMPs in Uganda need to bolster their human capital through recruitment strategies that target experienced Supervisor-level staff, and recruiting those with CPA or ACCA qualification would be an added competitive advantage. Future studies into human capital in SMPs should cover staff development, deployment and retention strategies. Keywords: Human capital, recruitment, strategies, competitiveness, Small and Medium-sized Practice